Lanscape Architecture of Culinary Tourism Objects In Paddy Field Areas - Syam, Fariz Harindra; Andriana, Melly; Ardianti, Syahna Dwi (Journal of Community Research and Service, 2023)
This study focuses on the landscape architecture of culinary tourism objects in the paddy field area of Desa Kota Pari. The research aims to explore the potential of utilizing the natural and cultural elements of the site to create attractive and sustainable culinary tourism experiences.The study follows a qualitative descriptive approach, starting with an inventory stage to collect data on the existing conditions of the research location. Information about the unique motifs and ornaments of Desa Kota Pari is also gathered for the design and development concepts.The collected data is analyzed, considering physical and environmental, demographic, economic, and cultural aspects. From this analysis, various design and development concepts are formulated. These concepts include spatial zoning, tourist facilities, hardscape and softscape elements reflecting the local culture.Using 2D CAD applications and Photoshop, a site plan is created for the Pematang Sawah area, complemented by 3D visualizations. The research findings emphasize the potential of the paddy field area as a culinary tourism destination. By integrating the natural and cultural elements into the design, a sustainable and engaging experience can be created.